2012
DOI: 10.1111/j.1750-2659.2012.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased symptom severity but unchanged neuraminidase inhibitor effectiveness for A(H1N1)pdm09 in the 2010-2011 season: comparison with the previous season and with seasonal A(H3N2) and B

Abstract: Background  No studies of the clinical symptoms before starting therapy or of the effectiveness of neuraminidase inhibitors (NAIs) have been carried out of the 2009–2010 and 2010–2011 seasons that compare A(H1N1)pdm09 or the three circulating types of influenza virus. Methods  The clinical symptoms and duration of fever (body temperature ≥37·5°C) after the first dose of an NAI (oseltamivir, zanamivir, laninamivir) were analyzed. PCR was carried out for 365 patients with A(H1N1)pdm09 in the 2009–2010 season and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…An overview of the studies (Table and Table ) showed a lot of diversity in the populations that were investigated: Studies are presented in terms of hospitalized patients (n = 22) or cover mainly outpatient settings (n = 19), such as primary care (n = 6) or community‐based (n = 4) settings. Most studies were carried out in Asia (n = 17), Europe (n = 15), or North America (n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of the studies (Table and Table ) showed a lot of diversity in the populations that were investigated: Studies are presented in terms of hospitalized patients (n = 22) or cover mainly outpatient settings (n = 19), such as primary care (n = 6) or community‐based (n = 4) settings. Most studies were carried out in Asia (n = 17), Europe (n = 15), or North America (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…The influenza viruses that were most frequently compared were A(H1N1)p versus A(H3N2) (n = 23), influenza A versus B (n = 18), and A(H1N1) versus A(H3N2) (n = 12). The proportion of influenza patients that had received the vaccine was reported in 24 studies, but RR estimates were adjusted for vaccination status in only four papers . Vaccinated patients were excluded from the analyses in four studies, and no or insufficient information on patients’ vaccination status was available in 19 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug is retained in the respiratory tract for up to 6 days after a single inhalation [69, 70]. After the licensure, it is generally observed that laninamivir is as equally effective as the other three NAIs against influenza A(H1N1)pdm09, A(H3N2), and B to children and adults [7175]. …”
Section: National Influenza Surveillancementioning
confidence: 99%
“…Analyses of vital statistics data from the United States and South Africa have suggested that the numbers of excess deaths associated with influenza are higher in years when influenza A(H3N2) virus is circulating than when influenza B or prepandemic influenza A(H1N1) virus is circulating ( 4 , 7 ). Some studies have suggested that influenza A(H1N1)pdm09 virus infection led to more severe outcomes than did other types and subtypes ( 8 , 9 ). In the first 3 months after influenza A(H1N1)pdm09 virus was identified in South Africa, 91 deaths among 12,331 patients with laboratory-confirmed cases were identified; rates of HIV infection and pregnancy among those who died were high ( 10 ).…”
mentioning
confidence: 99%